Decolonization of Kazakhstan - Mustoyapova, Ainash. author. (orcid)0000-0001-5658-9844 Link aut Link
XIII, 304 p. 1 illus.
Keywords: This book is devoted to the problem of the decolonization of Kazakhstan, which is considered in the framework of postcolonial studies. The author raises issues of identity, historical and socio-cultural heritage of nomads. In addition, the book examines and destroys colonial and Soviet myths and stereotypes concerning the history, lifestyle and traditions of the Kazakhs. Considering that imperial sentiments are increasing in Russia (as a former metropolis), the process of decolonization seems to be urgently necessary for Kazakhstan. And this process is beginning to develop actively. This fascinating polemic will interest historians, scholars trying to understand the former Soviet space, and scholars of Eurasia. Ainash Mustoyapova is Associate Professor at Karaganda Buketov University. She is the author of more than 60 scientific and educational publications (Kazakhstan, Great Britain, Poland, Ukraine, Uzbekistan, Kyrgyzstan, Russia,) and more than 150 journalistic articles.